New Zealand 2 [videorecording (DVD)] - Smith, Philip; Ledger, Chris (Pilot Productions, 2007)
Ian Wright sets off from Auckland to visit the hot springs of Rotorua and heads to the Bay of Islands; travels to Christchurch before heading to the sports capital, Queenstown. Zay Harding begins in the capital, Wellington and ends at Lake Te Anau.